Analgesic Effect of Serratus Anterior Plane Block After Thoracoscopic Surgery: A Randomized Controlled Double-Blinded Study - Shang LH; Xiao ZN; Zhao YL; Long B (Dove Medical Press, 2020)
Li Hua Shang, Zhen Nan Xiao, Ya Li Zhao, Bo Long Department of Anesthesiology, Shengjing Hospital of China Medical University, Shenyang 110004, People’s Republic of ChinaCorrespondence: Bo LongDepartment of Anesthesiology, Shengjing Hospital of China Medical University, Shenyang 110004, People’s Republic of ChinaTel +86-18940259927Email longbo_27@163.comPurpose: Fast-track surgery is a developing trend in medical care. It is a core challenge for clinical anesthesia to reasonably reduce the dosage of opioids and relieve postoperative pain. Serratus anterior plane block (SAPB) is a novel analgesic technique with such advantages as easy operation, good safety, and few side effects.Patients and Methods: In total, 60 patients aged 18 to 65 years who were diagnosed with lung cancer and scheduled for thoracoscopic resection were randomly assigned to receive SABP or local infiltration anesthesia. We analyzed the time within 48 hrs after operation to visual analogue scale (VAS) pain score of 4 or higher and the number of patients requiring additional analgesics at 6 hrs and 12 hrs after operation.Results: The estimated median time to VAS ≥ 4 was 4 hrs (1.32 to 6.68) in the control group and 11 hrs (6.71 to 15.29) in the SAPB group (log-rank test: P=0.008). The number of patients requiring additional analgesics at 6- and 12 hrs after operation was significantly lower in the SAPB group than that in the control group (P< 0.05).Conclusion: Compared with local infiltration, SAPB provided extended postoperative analgesia after thoracoscopic surgery with reduced consumption of additional analgesics in the early postoperative stage.Keywords: fast-track surgery, video-assisted thoracic surgery, serratus anterior plane block, analgesia, clinical anesthesia, randomized clinical trial